The Cultural Paradox of All-Male Performance: (Dis)Figuring the Third Beauty in the Studio Life’s Twelfth Night - Choi, Boram (Multicultural Shakespeare: Translation, Appropriation and Performance, 2024)
The aim of this article is to explore the ambiguous and unstable boundaries of gender images depicted in Studio Life’s Twelfth Night (2011) where male actors perform female characters similar to the practice on the Shakespearean stage. As Akira Uno, one of the influential illustrators of Japanese shōjo manga, participated in designing the stage set, costumes, and make-up of the characters, the production presents the effect of “the third beauty.” This is characterised by both masculine and feminine attributes while simultaneously being neither masculine nor feminine. This unique feature reflects the position of women in modern Japanese society, where representations of female gender and sexuality are often marginalised and oppressed under the male-dominated social atmosphere. Consequently, the image of female gender has been rigidly fixed and stereotyped according to traditional norms. In this setting, the effeminate and beautiful boys in an exotic place become surrogates for females, who can freely explore their gender and sexual identity within the illusory world, where both homoerotic and heterosexual relationships are explored. Studio Life’s Twelfth Night reflects this illusion by adapting the styles of shōjo manga, but the production seldom offers critical insights or questions on gender issues, especially in the context of the realities faced by Japanese women in daily life. This article examines descriptions of female characters performed by male actors and interviews with the director, Kurata Jun. The main focus is on how the artists perceive and express the concept of gender in relation to Japanese social conditions, demonstrated through their physical portrayals and gestures in all-male casting.